Implementation of Sharia Regulations and Principles in Bullion Bank Operations: A Case Study of Gold Services in Sharia Banks - Kartika Marella Vanni; Riska Wijayanti (JURNAL AKTA, 2026)
This study analyzes the legal framework and the implementation of Sharia principles in bullion banking operations, particularly gold-based services provided by Islamic banks in Indonesia. Gold services, including gold savings, gold financing, and gold trading, have strategic potential to support product diversification and enhance the competitiveness of Islamic banking institutions. This research employs a normative juridical method using a conceptual approach and regulatory case studies. The analysis focuses on relevant legal instruments, including Law Number 21 of 2008 on Islamic Banking, regulations issued by the Financial Services Authority, and fatwas of the National Sharia Council–Indonesian Ulema Council concerning gold transactions. The findings indicate that, from a normative perspective, gold services are supported by a sufficient legal foundation through Islamic banking regulations and Sharia fatwas. However, Indonesia has not yet established a comprehensive and specific regulatory framework governing Islamic bullion banking operations. The implementation of Sharia principles in gold services is carried out through murabahah, ijarah, and wadi’ah contracts, emphasizing the existence of physical gold as the underlying asset and ensuring transparency in transactions. Despite this normative compliance, practical challenges remain, particularly regarding regulatory consistency, legal certainty, and the limited availability of physical gold storage infrastructure. Therefore, this study recommends regulatory refinement and stronger institutional coordination among the Financial Services Authority, Bank Indonesia, and the National Sharia Council to strengthen legal certainty and ensure effective compliance with Sharia principles in Islamic banking gold services nationwide.